2021
DOI: 10.1109/access.2021.3107055
|View full text |Cite
|
Sign up to set email alerts
|

Size-Reduction of a Dual-Band Circularly Polarized Dielectric Resonator Antennas

Abstract: In this paper, the size reduction of a dual-band circularly polarized (CP) Y-shaped dielectric resonator antenna (YDRA) is performed. Unlike the conventional CP DRAs, the circular polarization in the YDRA is achieved by the combination of linearly varying E-fields in the two arms of unequal length. Therefore, a PEC boundary condition based technique is applied to the long arm of the dielectric resonator (DR). As a result, a 33.18% reduction in the size is achieved after the optimization of the DR for the requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Apart from the above CP MIMO antenna design, dielectric resonator (DR) based antennas have also been studied as they can yield a much wider CP bandwidth [18][19][20][21][22][23]. Amid these designs, desirable CP radiations are generated by applying the following techniques, such as the L-type feeding network [18], 45 o truncation of diagonally placed DR element [19] for 5G applications, Y-shaped DR [20] for WLAN and WiMAX, offset feeding and asymmetrical cut [21] for 5 GHz WLAN, alignment of DR material with zero distance [22] for (7.72-8.08 GHz), and parasitic patch with DR element [23] for WiMAX applications. However, it is notable that the DRbased antennas are bulky in construction and exhibit a high profile due to the thickness of DR material.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the above CP MIMO antenna design, dielectric resonator (DR) based antennas have also been studied as they can yield a much wider CP bandwidth [18][19][20][21][22][23]. Amid these designs, desirable CP radiations are generated by applying the following techniques, such as the L-type feeding network [18], 45 o truncation of diagonally placed DR element [19] for 5G applications, Y-shaped DR [20] for WLAN and WiMAX, offset feeding and asymmetrical cut [21] for 5 GHz WLAN, alignment of DR material with zero distance [22] for (7.72-8.08 GHz), and parasitic patch with DR element [23] for WiMAX applications. However, it is notable that the DRbased antennas are bulky in construction and exhibit a high profile due to the thickness of DR material.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the fundamental mode (T E x 111 ) is the closest mode to the resonance frequency. The calculated quality factor (Q-factor) for the said mode, with and without metallic loop carried out in eigenmode simulation setup [22,23], are 9247 and 11924, respectively. The low Q-factor, obtained in the case of metallic loop, is caused by the additional losses in the strip's copper material.…”
Section: Decoupling Structure (Mechanism and Sensitivity Analysis)mentioning
confidence: 99%